2008
DOI: 10.1080/01904160802244712
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur, Boron, and Zinc Fertilization Effects on Grain and Straw Quality of Maize and Sorghum Grown in Semi-Arid Tropical Region of India

Abstract: Experiments were conducted on-farm during two seasons (2003-2004) to determine the effects of sulfur (S), boron (B), and zinc (Zn) fertilization on the grain and straw quality of sorghum and maize grown under rainfed conditions in the semi-arid zone of India. The farmers' fields were deficient in S, B, and Zn; in addition the soils were low in organic matter and extractable phosphorus (P), but adequate in extractable potassium (K). Results showed that the applications of S, B, and Zn (SBZn) with nitrogen (N) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 14 publications
(20 reference statements)
3
29
1
Order By: Relevance
“…For example, in the on-farm experiments conducted to determine the effects of S, B and Zn fertilization on the grain and straw quality of sorghum and maize grown under rainfed conditions in the SAT region of India showed that the balanced mineral nutrition (BN) through combined application of S, B, Zn, N and P as compared to the FI (farmer's inputs) increased N, S and Zn concentrations in the grain and straw of these crops (Sahrawat et al 2008a). These results stress the importance of balanced mineral nutrition of crops for increased produce quality.…”
Section: Soil Test-based Nutrient Management: Effects On Crop Productmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in the on-farm experiments conducted to determine the effects of S, B and Zn fertilization on the grain and straw quality of sorghum and maize grown under rainfed conditions in the SAT region of India showed that the balanced mineral nutrition (BN) through combined application of S, B, Zn, N and P as compared to the FI (farmer's inputs) increased N, S and Zn concentrations in the grain and straw of these crops (Sahrawat et al 2008a). These results stress the importance of balanced mineral nutrition of crops for increased produce quality.…”
Section: Soil Test-based Nutrient Management: Effects On Crop Productmentioning
confidence: 99%
“…There is a relationship between soil health and food and feed quality which in turn impacts human and animal health. The importance of mineral nutrition of crops along with improved cultivars of crops and crop management cannot be overemphasized for producing nutritious food (Graham et al 2007;Parthasarathy Rao et al 2006;Sahrawat et al 2008a) and fodder (Kelly et al 1996;Sahrawat et al 2008a;Rattan et al 2009). …”
Section: Soil Test-based Nutrient Management: Effects On Crop Productmentioning
confidence: 99%
“…Similar studies with phosphorus (P) and potassium (K) supply are under way in common bean (Blair et al 2009a). It is known that in situations with multiple nutrient deficiencies, balanced plant nutrition (combined application of all nutrients that are deficient in the soil) is a prerequisite for improving productivity and nutritional quality of seeds of cereals (Rego et al 2007;Sahrawat et al 2008;Pirzadah et al 2010). …”
Section: Iron and Zinc Uptake Accumulation And Translocation To mentioning
confidence: 99%
“…Soil fertility is critical for enhancing productivity and crop and food quality 2,14 . Moreover, there is a direct connection between soil health and food quality, and in turn between food quality and human health via food chain 15 .…”
Section: Perspectivesmentioning
confidence: 99%